Revestimentos à base de amido na conservação de mangas Tommy Atkins associados a duas fontes de cálcio e a um agente oxidante em ambiente refrigerado - Alan Ferreira de França; Iranilson Silva dos Santos; Júlio Gomes Júnior; José Eldo Costa; Alex Danilo Monte de Andrade; Rogério Severiano de Melo (Revista Principia, 2018)
The objective of this work was to evaluate the potential of conservation post-harvest starch-based edible film coatings manioc on ‘Tommy Atkins’ mangoes under refrigerated storage. We used fruit from a market in Natal / RN, respecting maturation stage “de vez”. After that the mangoes were taken to the Laboratory of Soils and Plants of the Agricultural School of Jundiaí - EAJ, where they were selected, aiming at the standardization of color, size and weight. The experimental design was completely randomized, in a factorial scheme of 5 x 6 type, corresponding to different treatments of the fruit (without coating application; edible film spraying based on cassava starch; fruit spraying with edible film based on manioc starch + calcium chloride, fruit spraying with edible film based on manioc starch + calcium propionate, fruit spraying with manioc starch + potassium permanganate) in six periods (0, 5, 10, 15, 20, 25 days) in a refrigerated environment (12 ± 2, 85% RH ± 5), and four replicates. The results were submitted to analysis of variance, the means of comparison was done by the Tukey test (5% probability). It was verified that the treatments used were superior to the control from the 15th day of storage, to loss of mass, prolonging the shelf life of the fruit in 10 days, but with no effect for the associations with source of calcium and oxidizing agent.